Cardiovascular OCT Imaging - Jang, Ik-Kyung (Springer International Publishing : Imprint: Springer, 2015)
This book is a detailed review of optical coherence tomography (OCT) in cardiovascular practice. OCT enables cross-sectional and volumetric imaging of internal structure and pathology in biological tissues, thus performing an "optical biopsy", imaging pathology in situ and in real time without the need for excisional biopsy. OCT imaging has become a standard of care in ophthalmology and is an emerging imaging modality in cardiology, where it provides information that often cannot be obtained by any other means. This book provides readers who are not familiar with image interpretation and don't have enough background/knowledge with information on its clinical use and potential. Cardiovascular OCT Imaging is designed for busy interventional cardiologists and cardiologists to quickly become familiar with this emerging technology so that they can take advantage of its power to improve patient care and outcome. It will therefore be of great interest to all involved in interventional cardiology from trainees to practicing physicians and technologists.